Results of a Joint Epizootiological Survey of Transboundary Natural Plague Foci of the Russian Federation and Potentially Focal Territories of the Republic of Kazakhstan in 2019–2022 - A. M. Senichkina; I. N. Sharova; Sh. V. Magerramov; K. S. Zakharov; A. A. Kuznetsov; V. N. Chekashov; A. M. Porshakov; M. G. Korneev; M. V. Proskuryakova; Yu. V. Kislitsyn; A. I. Belyaev; I. B. Kim; et al. (Проблемы особо опасных инфекций)
Consolidation of the efforts in implementation of epidemiological surveillance and control over plague and other dangerous natural-focal infections is an essential aspect in ensuring epidemiological well-being as regards particularly dangerous infectious diseases in the territory of natural plague foci and potentially focal territories located within the borders of the Russian Federation and the Republic of Kazakhstan. The aim of the work was to carry out a joint epizootiological survey of the transboundary territories of the Volga-Ural sandy natural plague focus and the territory of the East Kazakhstan region of the Republic of Kazakhstan (RK) potentially focal for plague over the period of 2019–2022. Materials and methods. Samples of field materials, collected during the epizootiological survey of the territory of Kazakhstan, were studied using bacteriological, molecular-genetic, and immune-serological methods. Results and discussion. We have obtained the current evidence on the spatial-biocenotic structure, the circulation of pathogens of dangerous natural-focal infectious diseases in the transboundary territories of Eastern and Western Kazakhstan. It has been established that the conditions that contribute to the possibility of human infection with plague and other dangerous infectious diseases in case of the aggravation of epizootic situation in the foci or importation of the pathogens into the territory are in place.